2000
DOI: 10.1021/ja000234i
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Entry to the Crambescidin Family of Guanidine Alkaloids. Enantioselective Total Syntheses of Ptilomycalin A, Crambescidin 657 and Its Methyl Ester (Neofolitispates 2), and Crambescidin 800

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 37 publications
0
57
0
Order By: Relevance
“…A library containing the natural products ptilomycalin A, batzelladine F, and 46 batzelladine-and crambescidin-based analogs (33,37,38) were initially screened by competition ELISA (Fig. 2 and Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A library containing the natural products ptilomycalin A, batzelladine F, and 46 batzelladine-and crambescidin-based analogs (33,37,38) were initially screened by competition ELISA (Fig. 2 and Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Batzelladine and crambescidin analogs were synthesized as described (33,(35)(36)(37)(38). Each compound was stored at Ϫ20°C at an average concentration of 10 mg͞ml in DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…9 The intriguing molecular structures and their significant biological activities have attracted considerable synthetic interest. The synthesis of a number of guanidine alkaloids have been reported, including ptilocaulin, 1,19 crambescins A, B, C1, and C2, 1 ptilomycalin A, crambescidins 657, 800, 9,20 and batzelladines D, 21 E, 22 F. 23 As part of our continuing efforts to identify biologically active marine natural products for development as antiinfective agents, we evaluated the highly active ethanol extract of the marine sponge Monanchora unguifera (de Laubenfels, 1953) (Order Poecilosclerida: Family Crambeidae) with the guidance of bioassays and obtained 1,8a;8b,3a-didehydro-8β-hydroxyptilocaulin (1) and its stereoisomer, new 1,8a;8b,3a-didehydro-8α-hydroxyptilocaulin (2) and mirabilin B (3). Barrow et al, and Patil et al reported the isolation of mirabilin B (3) from the sponge Arenochalina mirabilis and Batzella sp.…”
Section: Introductionmentioning
confidence: 99%
“…The deep red solution that formed was then stirred at -60 ºC for 1 h. The reaction was cooled (-78 ºC) and (R)-3-((tert-butyldimethylsilyl)oxy)-1-iodobutane 16 (8.26 g, 26.3 mmol) in THF (42 mL) was added and the reaction warmed to rt by removal of the cooling bath followed by stirring overnight. Water (90 mL) was added and the solution was separated and the aqueous fraction extracted with dichloromethane (3 × 50 mL), the combined extracts dried (MgSO 4 ) and concentrated by rotary evaporation to approximately 50 mL.…”
Section: Methodsmentioning
confidence: 99%